The Use of Cooperative Sources of Knowledge in Service Industry Companies - Soniewicki , Marcin (Studia Oeconomica Posnaniensia, 2014)
Knowledge and the processes of managing this resource are currently the principal elements of companies’ activities aimed at creating and maintaining their competitive advantage. The fundamental and primary process in this respect is the acquisition of knowledge. However, this is a complex issue as not every type of this resource can contribute to increasing the competitiveness of an enterprise. Cooperation with other companies provides an opportunity to access knowledge that is usually not widely available, which may actually increase an enterprise’s results. This issue is particularly significant for service industry companies due to the character of their operations. The findings from empirical research reveal an interdependence between the number of cooperative knowledge sources that are used by the enterprises from this sector and their competitiveness level. The results highlight the significance of using this sort of knowledge by service industry companies. The findings also indicate that the typical set of cooperative knowledge sources used by service industry companies differs depending on the specific characteristics of the services performed by an enterprise.